Phytochemical composition and biological activities of Dorcoceras uthongensis (Gesneriaceae) - A new species from the limestone karst of Suphan Buri, Thailand - Prajanban, Jaran; Patumchartpat, Wichai; Akkarawongsapat, Radeekorn; Napaswad, Chanita; Panvilai, Sathit (Journal of Phytology, 2024)
Dorcoceras uthongensis, a new species of the genus Dorcoceras Bunge, is described. This new species is endemic to Uthong district, Suphan Buri province, Thailand, and differs from the other species by exhibiting capitate glandular hairs with globose unicellular head on the abaxial surface of the leaf. Additionally, it is classified as an endangered species (EN) according to IUCN criteria. The phylogenetic analysis based on nuclear ITS1-5.8S-ITS2 confirmed its placement within Dorcoceras. Moreover, we sought to explore the potential biological activities of the crude extract of this new species. We evaluated the aqueous extract of leaves which revealed antioxidant activity and no cytotoxicity indicating potential safety for further research and utilization. To examine the phytochemical composition, we performed an analysis using LC-MS/MS-QTOF. The result revealed the presence of flavonoids, alkaloids, phenolic compounds, and terpenes.